2020
DOI: 10.1002/jbm.b.34692
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing electrospun nanofibers to recapitulate hierarchical fibrous structures of meniscus

Abstract: The meniscus has complex biomechanical functions endowed by the hierarchical fibrous structure of its extracellular matrix (ECM), which plays a central role in protecting the knee joint. However, it is challenging to recapitulate the ECM structure of the meniscus. Herein, we used electrospinning to prepare various scaffolds with distinct nanofibrous structures to approximate that of the heterogeneous ultrastructure of meniscus ECM. Our results showed that adjusting the deposition manner of nanofibers during el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
(146 reference statements)
2
23
0
Order By: Relevance
“…It was found that the crystallinity of C-CNF was higher than that of W-CNF due to the higher crystal structure of cotton [16,17], which were consistent with the results of SEM analysis in Section 3.1. The crystallinity of W-CNF was higher than that of MCC, and the crystallinity of MCC was higher than that of WC [18,19]. Different calculation methods of these three could result in different crystallinity calculation results, and perfect single crystal was extremely difficult to obtain.…”
Section: Crystallinity From Xrd Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…It was found that the crystallinity of C-CNF was higher than that of W-CNF due to the higher crystal structure of cotton [16,17], which were consistent with the results of SEM analysis in Section 3.1. The crystallinity of W-CNF was higher than that of MCC, and the crystallinity of MCC was higher than that of WC [18,19]. Different calculation methods of these three could result in different crystallinity calculation results, and perfect single crystal was extremely difficult to obtain.…”
Section: Crystallinity From Xrd Analysismentioning
confidence: 98%
“…The research on corn, wheat, shell, and reed in the terahertz frequency spectrum characteristics was at 0.2-1.8 THz. The results showed that the using of the terahertz wave technology for plant cellulose detection could achieve quick judgment of cellulose in biomass materials [16][17][18]. Luo et al [19] calculated 0.2-1.0 THz spectrum absorption coefficient and refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…[59][60][61][62][63][64] Recently, we adopted this technique to fabricate an electrospun nanofiber yarn scaffold, where rabbit meniscus cells infiltrated the full depth of scaffolds within 3 weeks. 54 A considerable increase in the population of cells with a uniform distribution of meniscus cells within the nanofiber yarn scaffold was observed after 5 weeks. Moreover, meniscus cells secreted extracellular matrix products within the nanofiber yarn scaffold, which profoundly improves the tensile strength of scaffolds with respect to the unseeded scaffolds.…”
Section: Enhancing Cell Infiltration Into Electrospun Scaffoldsmentioning
confidence: 94%
“…Therefore, we tested this hypothesis in a recent study by recreating the circumferential collagen fibril bundles via electrospinning with a dynamic liquid collection system. 54 We electrospun poly(L-lactic acid-cocaprolactone) (PLLA-CL)/decellularized meniscus extracellular matrix (dmECM) solution to prepare electrospun nanofibrous yarn scaffolds (Figure 3A). In addition, we also prepare aligned and random nanofibrous scaffolds via electrospinning.…”
Section: Similarities Between Meniscal Fibrous Structure and Electros...mentioning
confidence: 99%
“…fixed macrophage-seeded GT/PCL membranes (14 mm diameter) were embedded in paraffin at days 2, 4, and 6. Sections were stained with hematoxylin and eosin (H&E) (Wang et al, 2021).…”
Section: Paraformaldehydementioning
confidence: 99%